2017
DOI: 10.5194/bg-2017-470
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

N and P as ultimate and proximate limiting nutrients in the northern Gulf of Mexico: Implications for hypoxia reduction strategies

Abstract: Abstract. The occurrence of hypoxia in coastal oceans is a growing problem worldwide and clearly linked to anthropogenic nutrient inputs. While the need for reducing anthropogenic nutrient loads is generally accepted, it is costly and thus requires scientifically sound nutrient-reduction strategies. Issues under debate include the relative importance of nitrogen (N) and phosphorus (P), and the magnitude of reduction requirements.The largest anthropogenically induced hypoxic area in North American coastal water… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 34 publications
4
28
0
Order By: Relevance
“…It has also been suggested that phytoplankton growth can be limited by phosphorus during the period of hypoxia formation (Quigg et al, ; Sylvan et al, ). By using a spatially explicit physical‐biogeochemical model, Fennel and Laurent () concluded that N and P as ultimate and proximate limiting nutrients in the nGOM, respectively. In our study, the stoichiometric ratios of the ΔDIN biol and ΔSRP biol in the two plumes (51.91 ± 3.51 and 56.6 ± 6.85; Figure c) were significantly higher than the Redfield N:P uptake ratio of 16 (potential P limitation).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that phytoplankton growth can be limited by phosphorus during the period of hypoxia formation (Quigg et al, ; Sylvan et al, ). By using a spatially explicit physical‐biogeochemical model, Fennel and Laurent () concluded that N and P as ultimate and proximate limiting nutrients in the nGOM, respectively. In our study, the stoichiometric ratios of the ΔDIN biol and ΔSRP biol in the two plumes (51.91 ± 3.51 and 56.6 ± 6.85; Figure c) were significantly higher than the Redfield N:P uptake ratio of 16 (potential P limitation).…”
Section: Resultsmentioning
confidence: 99%
“…The atmospheric CO 2 concentration is expected to continuously increase in the future, while the eutrophication state in the nGOM can be significantly affected by management of anthropogenic nutrient loads (Fennel & Laurent, ; Justic et al, ; Justić et al, ; Rabalais et al, ). In order to investigate the combined impact of atmospheric CO 2 increase and varying eutrophication conditions, we used the multiple end‐member mixing model to simulate the changes in pH and Ω Ar under two future scenarios relative to the present condition (atmospheric CO 2 = 405 ppm; the present eutrophication status was set as the 100% eutrophication condition).…”
Section: Resultsmentioning
confidence: 99%
“…The main differences between model and satellite chlorophyll are in the coastal region. Those differences can be explained (in part) by satellite chlorophyll overestimation, due to the high concentration of dissolved colored organic matter and sediments associated with river runoff (Hu et al, 2000;Del Castillo et al, 2001;Gilbes et al, 2002;D'Sa and Miller, 2003). The greatest chlorophyll concentration values are within the MS river delta, and the lowest values within the region influenced by the Loop Current.…”
Section: Biogeochemical Model-data Comparisonmentioning
confidence: 99%
“…The model does not include phosphate as a limiting nutrient for phytoplankton growth. Although previous studies have indicated the existence of phosphate limitation near the MS-A deltas during May-July (Sylvan et al 2006(Sylvan et al , 2007Laurent et al, 2012;Laurent and Fennel, 2014;Fennel and Laurent, 2017), we focus here on the role of N and Si, as observational studies suggest that N and Si can modulate phytoplankton production and composition across the northern GoM (Dortch and Whitledge, 1992;Nelson and Dortch, 1996;Lohrenz et al, 1997;Rabalais et al, 2002;Zhao and Quigg, 2014).…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation